Large-scale implementation and adoption of the Finnish national Kanta services in 2010–2017: a prospective, longitudinal, indicator-based study - Jormanainen, Vesa (Finnish Journal of eHealth and eWelfare, 2018)
In Finland, implementation and adoption of the national Kanta services’ second phase services were carried out step-by-step from May 2010 till December 2017. The Kanta services currently include integrated, interoperable health information from EMR, EHR, PHR and social welfare sources that can benefit patients, care providers and policy makers. In Finland, the Ministry of Social Affairs and Health steers the Kanta services, and was responsible of the first phase implementation activities since July 2007. For the second phase of implementation and adoption of the services, a new national operational coordination function was established by law in January 2011. The adoption and implementation of the Kanta services would not have been possible without joint efforts of stakeholders and provision of adequate (state) funding. A set of indicators for various prospective, longitudinal monthly follow-up were used. The current principal Kanta services include My Kanta Pages (since May 2010), Prescription Centre (May 2010), Pharmaceutical Database (May 2010), Patient Data Repository and Patient Data Management Service (November 2013), Kelain (September 2016), and Client Data Archive for Social Welfare Services (May 2018) and Kanta Personal Health Record (May 2018).